Anti-NMDA encephalitis secondary to an ovarian teratoma presenting as altered mental status in a 32-year-old woman: A case report - Grace Jarmoc; Candace Smith; Emma Finnerty; Nyia L. Noel; Ariel Marks (Elsevier, 2024)
NMDA-R encephalitis is an autoimmune encephalitis that is known to be associated with ovarian teratomas. Eighty to 100 % of patients initially present with neuropsychiatric symptoms. Early recognition and intervention are critical to management and prognosis. This case demonstrates non-specific presenting symptoms of NMDA-R encephalitis.A 32-year-old woman presented to the emergency room with headache, nausea, vomiting, and photophobia. She was discharged with probable aseptic meningitis. Eight days later, she represented with delusional thought content, perseverative speech, and bizarre behavior. Cerebrospinal fluid studies showed elevated protein and mild pleocytosis. A computed tomography scan with contrast showed a 35-mm complex cystic lesion in the right adnexa, which was resected. Confirmatory pathology showed a mature cystic teratoma. Paraneoplastic panel later resulted positive for NMDA-R encephalitis. The patient was treated with methylprednisolone, IVIG, plasmapheresis, and rituximab. The clinical course was complicated by a hypersensitivity reaction to rituximab, non-convulsive status epilepticus requiring intubation, dysphagia requiring a PEG placement, a rectal ulcer causing acute blood loss anemia requiring multiple blood transfusions, bilateral hearing loss, and a left lung pneumothorax. The patient's mood, cognition, and motor function were favorably improving 19 months after diagnosis.This case illustrates presenting signs of NMDA-R encephalitis in a young woman as headache and altered mental status followed by psychosis and epilepsy. Treatment should involve a multidisciplinary team and be individualized and escalated in patients with worsening clinical status refractory to first-line therapy. Further research is warranted to understand the optimal treatment strategy for this disease.